Green alternatives to globalisation a manifesto - Woodin, Michael (London Pluto Press, 2004)
Essential reading for anyone wanting to move beyond critiques of economic globalisation to coherent and credible alternatives.' Dame Anita Roddick DBE 'Woodin and Lucas set out an eloquent and passionate argument which not only challenges the convenient assumption that economic globlisation is inevitable, but which also explodes the myth that globalisation benefits the poor.' Vandana Shiva 'A genuine alternative that promotes policies for people and the planet. If more politicians thought like this, we would live in a far better world.' Tony Juniper, Executive Director, Friends of the Earth (UK) Written by two of the UK Green Party's most inspirational figures, this book is an accessible and concise statement of the Green alternatives to economic globalisation. Arguing that globalisation increases poverty, undermines democracy, and destroys the environment, the authors demonstrate the urgent need for a new approach - economic localisation - that is based on the Green principles of equity, ecology and democracy. Michael Woodin and Caroline Lucas show how economic localisation could be adopted and applied to help solve many of the current international crises, including climate change, trade and development, agriculture, and international security.
Includes bibliographical references (p. 238-249) and index.
Keywords: International economic relations